Deep brain stimulation for people with Alzheimer's disease: Anticipating potential effects on the tripartite self. (November 2019) - Viaña, John Noel M.; Gilbert, Frederic
Memory dysfunction and cognitive impairments due to Alzheimer's disease can affect the selfhood and identity of afflicted individuals, causing distress to both people with Alzheimer's disease and their caregivers. Recently, a number of case studies and clinical trials have been conducted to determine the potential of deep brain stimulation as a therapeutic modality for people with Alzheimer's disease. Some of these studies have shown that deep brain stimulation could induce flashbacks and stabilize or even improve memory. However, deep brain stimulation itself has also been attributed as a potential threat to identity and selfhood, especially when procedure-related adverse events arise. We anticipate potential effects of deep brain stimulation for people with Alzheimer's disease on selfhood, reconciling information from medical reports, psychological, and sociological investigations on the impacts of deep brain stimulation or Alzheimer's disease on selfhood. A tripartite model of the self that extends the scope of Rom Harré's and Steve Sabat's social constructionist framework was used. In this model, potential effects of deep brain stimulation for Alzheimer's disease on Self 1 or singularity through use of first-person indexicals, and gestures of self-reference, attribution, and recognition; Self 2 or past and present attributes, knowledge of these characteristics, and continuity of narrative identity; and Self 3 or the relational and social self are explored. The ethical implications of potential effects of deep brain stimulation for Alzheimer's disease on the tripartite self are then highlighted, focusing on adapting informed consent procedures and care provided throughout the trial to account for both positive and negative plausible effects on Self 1, Self 2, and Self 3.